Factors of tooth extraction among adult patients attending in exodontia department of Dhaka Dental College and Hospital (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
In the management of the adult dental patient efforts are geared towards the preservation of permanent dentition as it is important for maintaining normal occlusal relationship, play role in aesthesis, speech, influence food habit and nutrition. This hospital based descriptive type of cross sectional study was done at Exodontia Department of Dhaka Dental College and Hospital to identify the factors that contribute in tooth extraction among the respondents. The study was carried out during the month of January to June 2009 and 110 respondents selected purposively. The study showed the majority of the respondents (57.3%) were in the age group of 20-39 years. Their mean age was 36.85.years, SD of age was ±13.85 and age range was 15-85 years. Among the respondents 46.4% were male and 53.6% were female. Dental caries was the leading cause of tooth extractions in 68% cases. It was also observed that post filling complication contributed in 33% cases of extraction. Patient requests due to economic cause in 16% cases, negligence in 11% cases and even distance of the treatment centre from residence reported in 15% cases. The treatment philosophy of the centre played a vital role. Heavy rush of the patient and inconvenient conservative treatment schedule caused many unnecessary extractions DOI: http://dx.doi.org/10.3329/bjodfo.v2i1.15996 Ban J Orthod & Dentofac Orthop, October 2011; Vol-2, No.1, 7-10